Global incidence of helminthic contamination of vegetables, cucurbits and fruits: A systematic review and meta-analysis. (March 2022) - Eslahi, Aida Vafae; Olfatifar, Meysam; Karim, Md Robiul; AbuOdeh, Raed; Modirian, Ehsan; Houshmand, Elham; Abdoli, Amir; Samimi, Rasoul; Sotoodeh, Simin; Mahmoudi, Razzagh; Hajialilo, Elham; Hashemipour, Sima; et al.
Abstract: Accidental ingestion of infective stages of helminths through consumption of contaminated vegetables and fruits causes a wide range of food-borne diseases in humans. This systematic review and meta-analysis evaluated the global incidence of helminthic contamination of vegetables, cucurbits and fruits . Several databases (Science Direct, Web of Science, PubMed, Scopus, and Google Scholar) were searched for literature published prior to November 2020. Overally, 184 articles (32 countries) met the inclusion criteria. Among these, 137 studies documented helminthic contamination in vegetables, 46 in cucurbits and 9 were in fruits. The pooled incidence (95% confidence interval) was 31% (26%–37%) for vegetables, 20% (14%–27%) for cucurbits and 20% (8%–37%) for fruits. The highest incidence rate was found in the Western Pacific WHO region (54%; 9%–95%). The most prevalent parasitic agents were Ascaris lumbricoides eggs (12%; 9%–15%) and Strongyloides stercoralis larvae (12%; 8%–16%) in vegetables, S . stercoralis larvae (10%; 5%–15%) and Toxocara spp. eggs (10%; 3%–21%) in cucurbits, and Trichuris trichiura eggs (9%; 1%–22%) in fruits. The highest incidence rate was found to be associated with lower-middle income countries (34%, 28%–41%) and regions with a tropical rainforest climate (50%, 10%–91%). The potential role of vegetables, cucurbits, and fruits in the spread of helminthic parasites was revealed. Utilizing clean water for irrigation, proper washing and cooking of vegetables and improved sanitary practices can decrease the public health hazard regarding the consumption of vegetables, cucurbits, and fruits. Highlights: We estimated the global incidence of helminthic contaminated vegetables, cucurbits, and fruits. The prevalence was 31%, 20%, and 20% for vegetables, cucurbits and fruits, respectively. The highest prevalence rate was in Western Pacific WHO region 54%. The highest helminthic contamination was related to tropical rainforest climate 50%.